Valorización del suero de queso para la obtención de aceites unicelulares de interés industrial. - Solórzano Guerrero, Amayaseth Elizabeth (2025)
The objective of this project was to utilize cheese whey as a substrate for the production of singlecell oils of industrial interest, using the oleaginous fungus Mortierella isabellina, known for its high lipid-producing capacity. A mixed and experimental methodology was employed, focused on lipid production. Mortierella isabellina was isolated from a soil sample containing decomposing plant matter, and after seven days, a pure culture of this oleaginous fungus was obtained. To enhance lipid production, fresh cheese whey was deproteinized. The physicochemical properties of both deproteinized and untreated cheese whey were going to be evaluated. Key properties included a pH of 5.45 for the deproteinized whey compared to 6.26 for the untreated whey and total solids of 6.02% and 7.14%, respectively. Protein content in the deproteinized whey was removed entirely (0.00%) compared to 2.24% in the untreated sample—an essential step, as protein can interfere with microorganism growth. Mortierella isabellina was cultivated in deproteinized whey enriched with carbon (glucose) and nitrogen (yeast) sources. The culture was conducted in three Erlenmeyer flasks labeled TG1, TG2, and TG3. After seven days of incubation, results showed that the highest lipid concentration was achieved in treatment TG3, with 11.53% lipids. The findings demonstrate that Mortierella isabellina is a viable source for obtaining singlecell oil from agro-industrial waste such as cheese whey. Although the oil was produced at a laboratory scale, the process can be scaled up for industrial applications. This oil has potential uses in various industries, including pharmaceuticals and cosmetics, and represents a viable option for the formulation of new food products.